The application of the IT support tools set in the irrigated area operation - Ekaterina A. Volkova (Мелиорация и гидротехника)
Purpose: scientific and technical substantiation and development of engineering and reclamation solutions related to the application of the IT support tools set for the irrigated area operation. Materials and methods. The tasks to be solved using IT tools were defined as planning on-farm water use, operational irrigation management and technical operation of the equipment and structures used in irrigated areas. The IT tools used were based on the developments of Novocherkassk Engineering and Land Reclamation Institute – branch of the Don State Agrarian University. Results. A structure for the integrated application of IT support tools for the tasks of operating an irrigated area has been developed. It included: simulation of operational modes of irrigation of agricultural crops, completing schedules of water supply and water consumption of an irrigated area; calculation of planned indicators of water use of an irrigated area; calculation of schedules for technical maintenance of sprinkler equipment; operational irrigation management; water distribution management in the irrigated area in accordance with its design and technical features; support for the tasks of operational operation of the sprinkler machines available on the site. The IT applications proposed to solve these problems ensure the use of a single information base for all, the use of publicly available technical IT tools, the use of a single user interface and operating rules for all. Conclusions. The conducted studies confirmed the relevance of using IT tools that allow both autonomously solving specific problems of operating irrigated areas and ensuring their comprehensive use, thereby ensuring the implementation of a systems approach to their operation, as a whole. At the same time, these tools should be oriented towards the possibility of their use by the operating personnel of the irrigated areas.